The Principle of Single-phase Doubly Salient DC Generator for Distributed Generation and its Transient FEM Analysis - 万伟悦; 严仰光; 孟小利 (Kongzhi Yu Xinxi Jishu)
Distributed Generation (DG) means the way to supply electric power by small-scale generators in some key parts of the public power system or near the electricity load. Proper development of DG is beneficial to economizing on energy consumption and protection environment. This paper proposes single-phase Doubly Salient Generator (DSG) as the major generator of the small-scale distributed DC power supply system due to the compact construction, high ratio between power and weight and high speed, which can simplify the system, reduce the cost and improve the reliability. First, the principle and topology of this type are introduced??then electromagnetic computation for this machine with transient Finite Element Method (FEM) is implemented. The external characteristics and output power characteristics of wound field and permanent magnet 4 poles /6 poles single phase DSGs and wound field 6 poles /4 poles three phase DSG are analyzed and compared respectively, even including the three generation methods of wound field 4 poles /6 poles single phase DSG. At last, the outputripple- voltage reduction methodology is simulated and verified..